The Complex Treatment Algorithm for Dry Eye Syndrome with Meibomian Gland Dysfunction. Combination of Intense Pulsed Light (IPL) with Eyelid Hygiene and Artificial Tears - D. Yu. Maуchuk; A. O. Loshkareva; T. V. Tsvetkova (Oftalʹmologiâ, 2020)
Nowadays, Meibomian gland dysfunction is considered as the leading cause of dry eye syndrome. Standard methods of the treatment rather often give us only shirt term remission, that’s why so actually to find new alternative treatment options with increasing of patients’ life quality and possibility for long-time remission. This study was directed to evaluate the effectiveness of complex dry eye treatment, included transdermal Intensive Pulse Light method, combined with preservative-free forms of eyelid hygiene and artificial tears eye drops. The  study involved 30 patients (60 eyes) with dry eye syndrome and meibomian gland dysfunction. There were included patients with severe conjunctival hyperemia, follicular reaction, meibomeitis with changed, heavy Meibomian glands secret, rough eyelid margin, telangiectasias, tear break-up time (Norn test) not more than 5 seconds, necessity of very frequent instillations of artificial tear eye drops. All patients in anamnesis had already received courses of antiinflammation, artificial tears therapy and had courses of eyelid hygiene (eyelid margin massage with glass stick) with short-term positive dynamic and returning of symptoms during one month. As a  result of studied algorithm, with a help of Intensive Pulse Light it was possible to decrease the period of positive dynamic receiving. From the other side, preservative-free forms of artificial tears eye drops (Hylaback) and  eyelid hygiene (Blephaclean TheaGel Steri-Free) gave the prolongation of positive effect.